Identifying Opportunities for Exploiting Cross-Layer Interactions in Adaptive Wireless Systems. (24th July 2007) - Weingart, Troy; Sicker, Douglas C.; Grunwald, Dirk
Abstract : The flexibility of cognitive and software-defined radio heralds an opportunity for researchers to reexamine how network protocol layers operate with respect to providing quality of service aware transmission among wireless nodes. This opportunity is enhanced by the continued development of spectrally responsive devices—ones that can detect and respond to changes in the radio frequency environment. Present wireless network protocols define reliability and other performance-related tasks narrowly within layers. For example, the frame size employed on 802.11 can substantially influence the throughput, delay, and jitter experienced by an application, but there is no simple way to adapt this parameter. Furthermore, while the data link layer of 802.11 provides error detection capabilities across a link, it does not specify additional features, such as forward error correction schemes, nor does it provide a means for throttling retransmissions at the transport layer (currently, the data link and transport layer can function counterproductively with respect to reliability). This paper presents an analysis of the interaction of physical, data link, and network layer parameters with respect to throughput, bit error rate, delay, and jitter. The goal of this analysis is to identify opportunities where system designers might exploit cross-layer interactions to improve the performance of Voice over IP (VoIP), instant messaging (IM), and file transfer applications.